Targeting the Key Signaling Pathways in Breast Cancer: From Molecular Mechanism to Therapeutic Interventions - Singh, Deepika; Sahoo, Ankit (Recent Patents on Anti-Cancer Drug Discovery, 2025)
Breast cancer is a public health issue in developing and developed countries. Nowadays, the concept of BCSC (breast cancer stem cell) is gaining popularity among oncology researchers. The breast cancer stem cell is a tiny cell fraction inside the tumor mass that shows features that look like stem cells that are implicated in the genesis, recurrence, and metastasis of breast cancer tumors. Extracellular cues, mutations, and epigenetic control all contribute to the intricacy of gene expression control in Breast cancer stem cells. Thus, signaling pathways identified in breast cancer are Hedgehog and NOTCH, signal transducer and transcription 3, wingless-type MMTV integration site family (Wnt)/-catenin, and nuclear factor-kappa B, particularly connected with a phenotype of stem cell. Furthermore, the tumor microenvironment, such as hypoxic regions, can impact these BCSCs. Various approved signaling pathway targeted molecules have been patented, which show protective effects against breast cancer and have been used in clinical uses. PARP inhibitors are found to be very useful in the treatment of breast cancer. Promoting studies on the molecular pathways underlying the development of cancer in breast cancer patients was one of the main objectives of this study topic. The objective of this review Topic was to discover new intrinsic and extrinsic molecular pathways. Research focusing on novel signaling pathways that may lead to novel treatments or identifying patients at-risk of not responding to standard therapy approaches were the areas of focus we highlighted. The paper covers the linkage between breast cancer stem cells and cellular signaling, the tumor microenvironment in BC, and the relevance of signaling pathways and their therapeutic interventions. The review also covered patent applications associated with these signaling pathways and their prospects.
Keywords: triple-negative breast cancer (TNBC)